Decision-making in the public administration: a dialogue of rationalities - de Carvalho, Elisabete (2013)
The Science of Public Administration has been the stage for a heated debate on thesearch for the management models and organisational designs that best suit asystem which will simultaneously achieve the goals that are set for it and make appropriateuse of the resources at its disposal. The desired end is an instrumental,managerial rationale derived from a theoretical modelling of the decision-makingprocess that is widely adopted in both management and economic fields: the rationaldecision-making model. However, it is not entirely clear that this model matcheswhat actually happens in the reality it seeks to describe and explain. There areother models, born out of studies of an inductive, pragmatic nature, that providedifferent visions of and explanations for decision-making processes, particularlywhen two variables are introduced: the political context; and when decisions concernambiguous problems that tend to be complex. The author synthetically systematisesome of these models, in the hope that considering them may provide valuable assistance in the process of transforming the administrative systemeffectively.